LOW-COST RASPBERRY-BASED MOBILE PAYMENT SYSTEM FOR CASHLESS TRANSACTION IN GASOLINE STATION - Rahmat Septian Wijanarko; Meredita Susanty (Universitas Muria Kudus, 2019)
To embrace the cashless future, PT PERTAMINA collaborate with various banks and LinkAja!, one of e-finance services in Indonesia, to accept cashless payment using QR code technology using mobile application. The cashless payment now accepted in both conventional gas station and self-service gas station. However, at a self-service gas station, customers generally make payments before refueling to an operator located in the control post (before the dispenser area/refueling area). It requires the customer to return to the operator in order to request the change when they stop refueling before reaching the requested volume. This research proposes some modifications toward the fuel dispenser so that the dispenser is able to accept cashless payment, provide correct amount of fuel, and guarantee payment for each transaction even when there are no operators around. The implementation of this prototype improves service at gas station by reducing queue time about three to seven second per vehicle, improve company efficiency by reducing the number of operators in gas station from one operator per dispenser to one operator per station, also, it removes the balancing process performed by the operator at the end of the shift. Sales reports are generated automatically in near real-time.